A novel oligomer containing DOPO and ferrocene groups: Synthesis, characterization, and its application in fire retardant epoxy resin. (October 2018) - Wen, Yi; Cheng, Zhou; Li, Wenxiong; Li, Zhi; Liao, Duijun; Hu, Xiaoping; Pan, Ning; Wang, Deyi; Hull, T. Richard
Abstract: A novel oligomer (PFDCHQ) based on 9, 10-dihydro-9-oxa-10-phosphaphenanthrene −10-oxide (DOPO) and ferrocene groups was synthesized successfully, aiming at improving the flame retardant efficiency of diglycidyl ether of bisphenol A epoxy resin (DGEBA). FTIR, 1 H NMR and 31 P NMR were used to confirm the chemical structure of PFDCHQ. The high char yields of 60.3 wt% and 20.1 wt% were obtained for PFDCHQ from TGA results in nitrogen and air atmosphere, respectively. The thermal degradation mechanism of PFDCHQ was investigated by TG-FTIR and Py-GC/MS. The limiting oxygen index (LOI) of EP-5 with 5 wt% loading of PFDCHQ increased to 32.0% and the UL-94 V-0 rating was achieved, showing a notable blowing-out effect. In contrast to EP-0, the peak of the heat release rate (pHRR) and total heat release (THR) of EP-5 decreased by 18.0% and 10.3%. The flame retardant mechanism of PFDCHQ in epoxy resin was studied by TG-FTIR, SEM and Raman. SEM and Raman results indicated the formation of coherent and dense char residue with high degree of graphitization due to the incorporation of PFDCHQ. In UL-94, the blowing-out effect dominantly accounted for the enhanced flame retardancy in combination with optimized char structure. Furthermore, the addition of PFDCHQ improved the Young's modulus compared to EP-0. Highlights: A novel oligmer (PFDCHQ) based on DOPO and ferrocene groups was synthesized successfully. A possible thermal decomposition mechanism for PFDCHQ is proposed. The EP-5 composite containing 5 wt% PFDCHQ can easily achieve UL-94 V-0 rating with LOI value of 32% and improved T g . PFDCHQ shows a significant fire retarding effect both in condensed and gas phase.